FLASH with carbon ions: Tumor control, normal tissue sparing, and distal metastasis in a mouse osteosarcoma model. (October 2022) - Tinganelli, Walter; Weber, Uli; Puspitasari, Anggraeini; Simoniello, Palma; Abdollahi, Amir; Oppermann, Julius; Schuy, Christoph; Horst, Felix; Helm, Alexander; Fournier, Claudia; Durante, Marco
Graphical abstract: Highlights: FLASH radiotherapy with carbon ions was demonstrated for the first time in vivo. FLASH (100 Gy/s) reduced normal tissue toxicity and tumor growth. FLASH irradiation reduces the number of lung metastases. Abstract: Background and purpose: The FLASH effect is a potential breakthrough in radiotherapy because ultra-high dose-rate irradiation can substantially widen the therapeutic window. While the normal tissue sparing at high doses and short irradiation times has been demonstrated with electrons, photons, and protons, so far evidence with heavy ions is limited to in vitro cell experiments. Here we present the first in vivo results with high-energy 12 C-ions delivered at an ultra-high dose rate. Materials and methods: LM8 osteosarcoma cells were subcutaneously injected in the posterior limb of female C3H/He mice 7 days before radiation exposure. Both hind limbs of the animals were irradiated with 240 MeV/n 12 C-ions at ultra-high (18 Gy in 150 ms) or conventional dose rate (∼18 Gy/min). Tumor size was measured until 28 days post-exposure, when animals were sacrificed and lungs, limb muscles, and tumors were collected for further histological analysis. Results: Irradiation with carbon ions was able to control the tumour both at conventional and ultra-high dose rate. FLASH decreases normal tissue toxicity as demonstrated by the reduced structural changes in muscle compared to conventional dose-rate irradiation. Carbon ion irradiation in FLASH conditions significantly reduced lung metastasis compared to conventional dose-rate irradiation and sham-irradiated animals. Conclusions: We demonstrated the FLASH effect in vivo with high-energy carbon ions. In addition to normal tissue sparing, we observed tumor control and a substantial reduction of lung metastasis in an osteosarcoma mouse model.